 Thread starter
 #1
Please refer to the attached image.
for part
a) this is what i did:
$G = k$, $k1< X < k$
so I substituted $k1$ and $k$ into the given exponential rv,
this gave me
$\lambda e^{\lambda(k1)}$ and $\lambda e^{\lambda k}$
$= \lambda e^{\lambda(k1)} + \lambda e^{\lambda k}$
But I feel like I am on the wrong track.
This question is really hard for me to comprehend, could someone water it down for me a bit, or help me out?
Thanks in advance!
for part
a) this is what i did:
$G = k$, $k1< X < k$
so I substituted $k1$ and $k$ into the given exponential rv,
this gave me
$\lambda e^{\lambda(k1)}$ and $\lambda e^{\lambda k}$
$= \lambda e^{\lambda(k1)} + \lambda e^{\lambda k}$
But I feel like I am on the wrong track.
This question is really hard for me to comprehend, could someone water it down for me a bit, or help me out?
Thanks in advance!
Attachments

16.7 KB Views: 10